Conserving the unique aquatic ecosystem of the Jiuzhai National Heritage Site after the 2017 earthquake: Achievements and challenges - Xiong, Yujiu; Du, Jie; Qiu, Gouyu (Frontiers in Environmental Science, 2022)
Water resources are the key link within the unique landscape of the Jiuzhaigou World Natural Heritage Site. However, the earthquake on 8 August 2017 induced serious damage to the ecosystem of the Jiuzhaigou region. Water resource quantity was threatened by the direct destruction of the connectivity between the upstream and downstream river systems, whereas water quality and the original aquatic ecosystem were worsened indirectly by secondary disasters, such as landslides and debris flows triggered by earthquakes. It is urgent to protect water resources to maintain a healthy aquatic ecosystem for the Jiuzhaigou World Natural Heritage Site. Therefore, water resource protection strategies are developed by collaboratively considering water quantity, quality and aquatic ecology, including 1) studying the relationship between upstream and downstream in terms of water supply and connectivity, 2) developing emergency plans for extreme precipitation disasters and ecological water regulation schemes for extreme drought, 3) clarifying the impact of vegetation management measures on water conservation, nutrient cycling and water quality, 4) separating the contributions of earthquakes from related disasters, hydrodynamic changes, and lake bank vegetation succession to lake swamping, 5) identifying the potential water pollution risk caused by ecological restoration projects, analyzing the sources of pollutants such as nitrogen, phosphorus and atmospheric acid deposits and developing control measures, and 6) systematically evaluating aquatic ecological health and determining water ecological protection and restoration measures. This review may provide critical viewpoints for conserving aquatic ecosystems, not only in the Jiuzhai World Natural Heritage Site but also in other global conserved aquatic parks.